The Effect Of Additional Income On Performance In Dairi Regency Inspectorate Office - Heraldo Zinggra; Muhammad isa Indrawan (International Journal of Management, Economic and Accounting, 2024)
This study aims to analyze the effect of Additional Income on Employee Performance at the Dairi Regency Inspectorate Office. This study uses a causal associative quantitative method with the total population of 43 employees in the Dairi Regency Inspectorate Office, and the sampling technique used is a saturated sample where the entire population of 43 employees is used as a sample. Data was obtained through questionnaires distributed to employees from various divisions. The results of the study show that Additional Income has a positive and significant effect on Employee Performance. This is evidenced by a t-count value of 10.690 > t-table 1.68288, and a significance value of 0.000 < 0.05. The regression coefficient of 1,322 shows that every 1 unit increase in Additional Income will increase Employee Performance by 1,322 points, assuming other variables remain constant. The results of the determination coefficient test showed an Adjusted R Square value of 0.730 or 73%, which showed that Additional Income had a significant influence on Employee Performance, and the remaining 27% was influenced by other factors that had not been studied in this study. Overall, this study concludes that Additional Income can contribute positively to improving Employee Performance at the Dairi Regency Inspectorate Office.